Analisis Ketersediaan dan Kebutuhan Air Berdasarkan Neraca Air di Sub DAS Cikeruh Jawa Barat - Charina Agnesia; Edy Suryadi; Sohia Dwiratna Nur Perwitasari (Jurnal Agritechno, 2021)
The increasing of the population along with changes in land use in the Cikeruh sub-watershed will affect the availability and the demand water as well as the level of water fulfillment in crucial sectors, namely: domestic, non-domestic, agriculture, industry, animal husbandry, and fisheries. This study aims to find out the most recent data on water availability and demand to determine the condition of the water balance in the Cikeruh sub-watershed. The method used in this research is descriptive analysis. Water availability was analyzed using the mock method and water availability was analyzed using SNI 6728.1-2015, Circular Letter of the Ministry of Public Works and Public Housing Number 07 of 2018, and related previous studies. The results showed that the total water availability in the Cikeruh sub-watershed was 212.901.228,61 m3/year with an average water availability of 17.741.769,05 m3/month and a total water demand of 462.306.728,53 m3/year with an average water requirement of 462.306.728,53 m3/month. The Cikeruh sub-watershed experiences a water shortage (deficit) throughout the year. The highest water deficit occurred in October, that -29.057.550,95 m3/month and the lowest deficit occurred in February, that -1.459.819,23 m3/month. The water availability in the Cikeruh sub-watershed only can fulfill the water needs of the domestic, non-domestic, animal husbandry, and fishery sectors. The water availability in the Cikeruh sub-watershed has not been able to fulfill the water needs of the agricultural and industrial sectors.